Evaluating business performance : small business case studies - Auliffe, Mark; Sykes, Amanda; Learning Essentials (Bendigo, Vic. : Learning Essentials, 2006)
Explained the key concepts of business performance and students will gain an understanding of the accounting processes required to evaluate the business performance
Writer, associate producer, Simon Garner ; camera, Karen Ng, Nick Haywood
Voice over : Kelle Jones
For middle secondary to senior secondary students
Keywords: Corporations -- Finance; Business enterprises -- Finance; Strategic planning; Industrial management